Roadshow on Management of Scientific Publication in the Field of Health - Kasiati, Klanting (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Scientific publications in the field of health are necessary for stakeholders as the foundation for policy making in health development, but there are still many health scientists and health journal managers who face obstacles in realizing the publication of open access scientific articles. For this reason, FORIKES conducts social activities, namely: 1) assisting the writing of scientific articles for scientists and 2) providing unlimited training and assistance on the management of scientific publications through electronic journals. This activity has successfully increased the publication of scientific articles by health scientists and the implementation of electronic journals in the field of health in Indonesia.